TINGKAT KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL TIPE HIGHER ORDER THINKING SKILL DI TINGKAT SMA - Widayanti, Evi; Siahaan, Jetti Oktavia (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The aim of this research is to describe students' creative thinking abilities in solving Higher Order Thinking Skills type questions at the high school level. The type of research used by researchers is qualitative-descriptive research. The subjects in this research were Class XI students at SMA Wijaya Putra Surabaya. Meanwhile, to determine the object, the researcher used a sampling technique, namely purposive sampling, where the object was taken based on certain considerations. The data analysis technique that researchers will use is the Miles and Huberman model analysis technique. This model analysis technique is carried out interactively and continuously until the data is saturated. The steps that must be taken in this model analysis technique are data reduction, data presentation, and conclusions. The results of this research were that there were 25 subjects (90%) who were included in TKBK 0 (Not Creative). There are 3 subjects (10%) included in TKBK 1 (Less Creative). Students included in TKBK 1 are students who only meet one of the three indicators of creative thinking, namely fluency.